Topsoil compaction and recovery in integrated no-tilled crop–livestock systems of Argentina - Fernández, Patricia Lilia (2015)
Cattle trampling during grazing of crop residue may cause physical soil damage that may be repaired when animals are excluded. Understanding the interplay between soil deterioration and natural recovery of the soil physical condition allows for a better understanding of grazing management systems. Various soil physical properties (i.e., bulk density (BD), penetration resistance (PR), infiltration rate, structural instability) were determined up to 20 cm depth in a silty loam Typic Argiudoll and a sandy loam Typic Hapludoll of the Argentine Pampas from 2005 to 2008. Sampling was carried out before and after grazing, and at different moments of the crop cycle including harvest event. Grazing winter residues and weeds did not lead to the expected compaction processes (e.g., in average BD difference between after grazing and before grazing was from 0.072 to +0.137 Mg m3 for both soils under grazing). In general, physical soil conditions improved during winter, independently of grazing. This might be related to the intrinsic soil characteristics (organic matter content, moisture, clay content) or grazing system (stocking rate, duration of grazing period), which prevented soil physical damage, suggesting that recovery forces were greater than grazing stress. Cropping to maize and soybean showed similar value or improved soil physical properties respect to the after grazing (e.g., in average PR difference between before harvest and after grazing was from +409 to 2561 kPa for both soils), acting as biotic a recovery factor. However, massive damage was harvest operation led to the highest soil deterioration (e.g., in average PR difference between before harvest and after harvest was 985 kPa).